2018
DOI: 10.1002/elps.201700494
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pumping mechanism for non‐Newtonian blood flow with AC electrothermal forces in a microchannel by hybrid boundary element method and immersed boundary‐lattice Boltzmann method

Abstract: Efficient pumping of blood flow in a microfluidic device is essential for rapid detection of bacterial bloodstream infections (BSI) using alternating current (AC) electrokinetics. Compared with AC electro-osmosis (ACEO) phenomenon, the advantage of AC electrothermal (ACET) mechanism is its capability of pumping biofluids with high electrical conductivities at a relatively high AC voltage frequency. In the current work, the microfluidic pumping of non-Newtonian blood flow using ACET forces is investigated in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…þV c and -V c are applied on the electrodes while the other microchannel surfaces are electrically insulated. In addition, as the temperature gradient between electrodes is the most significant factor for inducing ACET flow as discussed in the references, 10,11,26 the left electrode (red color in Fig. 2) is thermally insulated while the right electrode (blue color in Fig.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…þV c and -V c are applied on the electrodes while the other microchannel surfaces are electrically insulated. In addition, as the temperature gradient between electrodes is the most significant factor for inducing ACET flow as discussed in the references, 10,11,26 the left electrode (red color in Fig. 2) is thermally insulated while the right electrode (blue color in Fig.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Recently, our group investigated the pumping mechanism of non-Newtonian blood flow under the AC electrothermal effect, and the results showed that the shear-thinning characteristic and excellent dielectric property of blood makes it highly appropriate for ACET pumping. 26 However, a two-dimensional (2D) numerical approach is used in this work so that the electrode configuration design at different microfluidic channel surfaces is…”
Section: Introductionmentioning
confidence: 99%
“…Hong et al developed a coupled model, compared it with the classical model, and found that only at small temperature rises do the results of the two models match [87]. More recently, pumping and mixing of non-Newtonian fluids have been studied [89,90,91].…”
Section: Theorymentioning
confidence: 99%
“…Finally, the data on the GPU should be copied to the host memory of CPU for printing at any specific time when the results are needed. During the recent years, LBM is demonstrated to be appropriate for GPU computing [147][148][149][150][151], and it has been applied to solve several different physical problems [152][153][154][155].…”
Section: Gpu Accelerationmentioning
confidence: 99%